2015
DOI: 10.1186/s12871-015-0056-2
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of combined epidural/general anesthesia during major abdominal surgery in patients with increased intracranial pressure: a cohort study

Abstract: BackgroundThe increased intracranial pressure can significantly complicate the perioperative period in major abdominal surgery, increasing the risk of complications, the length of recovery from the surgery, worsening the outcome. Epidural anesthesia has become a routine component of abdominal surgery, but its use in patients with increased intracranial pressure remains controversial. The goal of the study was to evaluate the safety and efficacy of epidural anesthesia, according to monitoring of intracranial pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…It has been demonstrated that general anesthesia may offer improved hemodynamic stability relative to regional anesthesia . Epidural anesthesia is known to be a routine component of abdominal surgery due to the high quality of analgesia and the early mobilization of patients, including patients at high risk for perioperative complications . Previous evidence revealed that combined general and epidural anesthesia provided better analgesia and a better reduction in blood loss and postoperative complications than general anesthesia .…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that general anesthesia may offer improved hemodynamic stability relative to regional anesthesia . Epidural anesthesia is known to be a routine component of abdominal surgery due to the high quality of analgesia and the early mobilization of patients, including patients at high risk for perioperative complications . Previous evidence revealed that combined general and epidural anesthesia provided better analgesia and a better reduction in blood loss and postoperative complications than general anesthesia .…”
Section: Introductionmentioning
confidence: 99%
“…No study on the effects of INB on elderly patients undergoing abdominal surgery has been performed. Continuous epidural anesthesia in combination with general anesthesia is recognized as an efficient approach for major abdominal surgery [13]. In this study, we found that epidural anesthesia in combination with general anesthesia provides better postoperative analgesia (in patients undergoing distal gastrectomy) as well.…”
Section: Discussionmentioning
confidence: 53%
“…Zabolotskikh and Trembach demonstrated a non-invasive method to determine ICP in 65 patients by using opthalmodynamometry wherein they concluded that a continuous epidural infusion with a low concentration of local anesthetic appears to be safe in patients with increased ICP [11]. The main limitation of this method is that it estimates only the trend of ICP while the abrupt changes may remain unnoticed.…”
Section: Discussionmentioning
confidence: 99%